Healthcare provider knowledge and attitudes about pre-exposure prophylaxis (PrEP) in pregnancy in Cape Town, South Africa - DAVEY, Dvora L. JOSEPH (AIDS Care, 2020)
Pre-exposure prophylaxis (PrEP) in pregnancy can reduce HIV incidence and reduce vertical HIV transmission. Healthcare providers (HCPs) play a critical role in delivering PrEP in antenatal care but little is known about HCP knowledge and attitudes to PrEP in pregnancy. We conducted a qualitative study in two healthcare facilities in Cape Town, South Africa to study to assess HCPs’ PrEP knowledge and perspectives relating to HIV prevention in pregnant women. Between January and March 2019, we administered semi-structured in-depth interviews among consenting antenatal HCPs. We investigated five domains of PrEP experiences/perspectives; each interview was audio-recorded and transcribed. We utilized a constant comparison approach to identify major qualitative findings. We enrolled 35 female HCPs (median age=43; median time as HCP=8 years). Fewer than half of HCPs had heard of PrEP before. Of those who had heard of PrEP, most felt that it was safe to take during pregnancy, though some were unsure. Most HCPs described inaccurate PrEP knowledge regarding effectiveness, and most who knew about PrEP lacked clinical detail. HCPs highlighted important potential barriers to maternal PrEP use including: fear that PrEP may be unsafe, or belief that women must talk to partners/parents before initiating PrEP. Potential facilitators of maternal PrEP use include relatively good knowledge about serodiscordancy and vulnerability to seroconversion in pregnancy, desire to help women gain control over their HIV prevention. HCPs working with pregnant women had limited knowledge about PrEP and expressed confusion about the effectiveness and safety of PrEP in pregnancy. We recommend integrating PrEP training into existing HIV testing and PMTCT nurse training and improve counseling and PrEP delivery for HIV-uninfected women in antenatal care.